Project Based on Problem (PoP) Learning Model: Improving Critical Thinking Skills in Elementary School Students - Novia Rahma Rista Utami; Ririn Setyowati (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
The Society 5.0 revolution demands resources that master 21st-century skills. Education is the primary means of improving the mastery of these skills. Based on the PISA data from 2022, students' abilities in the aspects of reading, science, and mathematics literacy, which measure students' critical thinking skills, are still in a very low category, ranking 69th out of 80 countries. In an effort to overcome this problem, education is implementing 21st-century skills in learning by developing a Project-Based Problem (PoP) learning model. This study aims to (1) explain the characteristics of the PoP learning model, (2) examine the feasibility of the PoP learning model, and (3) determine the effectiveness of the PoP learning model in improving the critical thinking skills of elementary school students. This study uses the research method of Borg and Gall with 10 development steps. The research subjects were 70 fifth-grade students from three elementary schools in Blora Regency. Data were obtained through critical thinking ability tests and student and teacher response questionnaires. Critical thinking ability data were analyzed based on a comparison of the post-test of the experimental and control groups through an Independent Sample T-Test gain score analysis with a significance level of 0.002, where α < 0.05, indicating a difference between the experimental and control groups. This indicates an increase in the critical thinking ability of fifth-grade students through the use of the PoP learning model at public elementary schools in Blora Regency